Wind work on oceanic mesoscale eddies in the Northeast Tropical Pacific Ocean - Teng, Fangyuan; Dong, Changming; Lim Kam Sian, Kenny Thiam Choy; Ji, Jinlin; Zhu, Weijun (Frontiers in Marine Science, 2023)
The transfer of atmospheric kinetic energy to the ocean is one of the major concerns in climate research. According to previous studies, the work of wind stress on oceanic mesoscale eddy is negative in most oceans, referred to as "eddy killing". However, another recent work, finds that the wind work on an eddy varies with interaction time. To better understand the wind work on eddies, the present study uses satellite remote sensing wind stress data and eddy data from 2000 to 2021 to investigate the effects of wind stress on eddies in the northeast tropical Pacific (NETP). The study demonstrates that the work done by the wind stress on eddies in this region varies seasonally and that there is a strong spatiotemporal link between the work done and the wind stress curl. The work of wind stress with positive (negative) curl on the entire area of a cyclonic eddy is positive (negative), and vice versa on an anticyclonic eddy. These results indicate that wind energy input is sensitive to wind stress curl, and eddies do not always hinder wind energy input in this area.